HPLC/DAD/ESI-MS 및 고체상 추출법을 이용한 뇨시료중 갑상선 호르몬 분석 - 표희수; 곽선영; 문명희 (한국분석과학회, 2006)
An analytical method for the determination of thyroid hormones in urine samples has been studiedby using solid-phase extraction and high-performance liquid chromatography/diode array detector/electro-sprayHypersil ODS column (4.6 m I.D., 100 mm length, particle size 5m) with ammonium formate bufer andacetonitrile, and UV spectra and mass fragment could be confirmed. The extraction recoveries of thyroidhormones in the urine samples (pH 3) were in the range of 89.0-113.1% with solid-phase extraction by C18,. Corresponding authorPhone : +82-(0)2-958-5181 Fax : +82-(0)2-958-5059E-mail: phs3692@kist.re.kr520 ...........Analytical Science & Technologyfollowed by elution with 4 ml of methanol/ammonium hydroxide (9 : 1). The calibration curves showed goodlinearity with the correlation coefficients (r2) varying from 0.992 to 0.998 and the detection limits of all analyteswere obtained in the range of 2-4 ng/ml (3.8-13.0 pmol/ml).